Identification of the maternal source of young‐of‐the‐year Arctic charr in Lake Hazen, Canada. (14th May 2013) - Sinnatamby, R. Niloshini; Reist, James D.; Power, Michael
Summary A discriminant function analysis model based on carbon and nitrogen stable isotope values was used to identify offspring of piscivorous large‐form and non‐piscivorous small‐form Arctic charr, Salvelinus alpinus, morphotypes from Lake Hazen, Nunavut, Canada. The ability to distinguish between morphotypes in Lake Hazen was based mainly on the separation of δ15N signatures because of adult occupation of significantly different trophic levels. A smaller difference between adult morphotype δ13C values, most likely combined with a potential increase in variation among individuals at the egg stage, a faster turnover rate in carbon relative to nitrogen and the size at which fish can be sampled in the open‐water season in Lake Hazen, probably contributes to the limited use of δ13C in distinguishing between morphotype offspring. Based on young‐of‐the‐year (YOY) origin estimates, the adult morphotypes were estimated to contribute approximately equally to the YOY population; however, the morphotype offspring were differentially distributed among sampled nursery sites. Unequal distribution corresponds with prerequisites suggested for the evolution of trophic specialists within a single population that experiences assortative mating based on trophic specialisation. Differential use of spawning areas and the more or less equal importance of both Lake Hazen forms found in this study, taken alongside previously noted morphological variation and available genetic evidence, suggest that Lake Hazen may be an example of early divergence relative to other Arctic charr populations described in the literature.